Ultrasonic Assisted Consolidation of Commingled Thermoplastic/Glass Fiber Rovings - Lionetto, Francesca; Dell’Anna, Riccardo; Montagna, Francesco; Maffezzoli, Alfonso (Frontiers in Materials, 2015)
Thermoplastic matrix composites are finding new applications in different industrial area thanks to their intrinsic advantages related to environmental compatibility and processability. The approach presented in this work consists in the development of a technology for the simultaneous deposition and consolidation of commingled thermoplastic rovings through to the application of high energy ultrasound. An experimental equipment, integrating both fiber impregnation and ply consolidation in a single process, has been designed and tested. It is made of an ultrasonic welder, whose titanium sonotrode is integrated on a filament winding machine. During winding, the commingled roving is at the same time in contact with the mandrel and the horn. The intermolecular friction generated by ultrasound is able to melt the thermoplastic matrix and impregnate the reinforcement fibers. The heat transfer phenomena occurring during the in situ consolidation were simulated solving by finite element (FE) analysis an energy balance accounting for the heat generated by ultrasonic waves and the melting characteristics of the matrix. To this aim, a calorimetric characterization of the thermoplastic matrix has been carried out to obtain the input parameters for the model. The FE analysis has enabled to predict the temperature distribution in the composite during heating and cooling The simulation results have been validated by the measurement of the temperature evolution during ultrasonic consolidation. The reliability of the developed consolidation equipment was proved by producing hoop wound cylinder prototypes using commingled continuous E-glass rovings and Polypropylene (PP) filaments. The consolidated composite cylinders are characterized by high mechanical properties, with values comparable with the theoretical ones predicted by the micromechanical analysis.